1981
DOI: 10.1007/bf00615408
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure liquid chromatographic determination of acetylsalicylic acid, salicylic acid, diflunisal, indomethacin, indoprofen and indobufen

Abstract: A high-pressure liquid chromatographic technique was developed which allowed concurrent measurement of acetylsalicylic acid (ASA) and salicylic acid (SA) in plasma. ASA was extensively deacetylated to SA not only in vivo but also in vitro, even in frozen plasma. The in vitro conversion could be prevented by physostigmine. In vivo, ASA was eliminated within few hours, whereas SA was continuously present following daily administration of conventional doses of ASA. A slight modification of a similar method, origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 11 publications
4
14
0
Order By: Relevance
“…Earlier studies (Eriksson et al, 1989;Verbeeck et al, 1979) had been carried out in ignorance of the sulphate conjugate, which is now known to account for 10-20% of the metabolism of single diflunisal doses (Loewen et al, 1988), and which has recently been shown to hydrolyse to diflunisal under certain acidic analytical conditions (Dickinson & King, 1989). Reproduction of the plasma diflunisal assays reported in the earlier studies gave, in our hands, circa 40-80% (Verbeeck et al, 1979) and 10-20% (Wahlin-Boll et al, 1981) hydrolysis of diflunisal sulphate (at circa 8 ,ug diflunisal equivalents ml-') after 1 min contact between diflunisal sulphate and the acidic aqueous/organic media. Thus plasma diflunisal concentrations seem certain to have been overestimated, and clearance underestimated, in those studies.…”
Section: Discussionsupporting
confidence: 56%
“…Earlier studies (Eriksson et al, 1989;Verbeeck et al, 1979) had been carried out in ignorance of the sulphate conjugate, which is now known to account for 10-20% of the metabolism of single diflunisal doses (Loewen et al, 1988), and which has recently been shown to hydrolyse to diflunisal under certain acidic analytical conditions (Dickinson & King, 1989). Reproduction of the plasma diflunisal assays reported in the earlier studies gave, in our hands, circa 40-80% (Verbeeck et al, 1979) and 10-20% (Wahlin-Boll et al, 1981) hydrolysis of diflunisal sulphate (at circa 8 ,ug diflunisal equivalents ml-') after 1 min contact between diflunisal sulphate and the acidic aqueous/organic media. Thus plasma diflunisal concentrations seem certain to have been overestimated, and clearance underestimated, in those studies.…”
Section: Discussionsupporting
confidence: 56%
“…However, as esterase inhibitors reduce the deacetylation of ASA (Wahlin-Boll et al, 1981), and as dipyridamole can function as an esterase inhibitor (Moncada & Korbut, 1979), it might enhance ASA concentrations following concurrent intake. Indeed, a previous study, based on a very small number of subjects (Brantmark et al, 1982), showed an increase, albeit statistically insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…Influence of ethanol on the bioavailability of ASA and SA Ten 18-to 45-year-old volunteers, five females and five males, all healthy according to conventional clinical and laboratory criteria, participated in two experiments, in random order, both times ingest- trifugation, plasma was prepared for high-performance liquid chromatography (HPLC) analyses of ASA and SA concentrations as described previously [9]. Pharmacokinetic (now including elimina-300-tion half-lives) and statistic analyses were carried out for ASA and SA as described for ethanol.…”
Section: Influence Of Asa Ibuprofen and Paracetamol On Ethanol Bioavmentioning
confidence: 99%